2016
DOI: 10.1063/1.4960963
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of primary and corner shock boundary layer interactions at mild back pressure ratios

Abstract: Unstart of rectangular inlets occurs as a result of interactions between shock-induced separation units along the floor/ceiling, corner, and sidewalls. While a significant body of literature exists regarding the individual flow interactions at the inlet floor/ceiling (called primary separation) and sidewalls, limited efforts have focused on the mean and dynamic features of the corner separation. Experiments are conducted to investigate primary and corner shock boundary layer interactions (SBLI) with the object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…None of the surface pressure correlations, consistently between the experiments and simulations, show any indication of a low-frequency unsteady connection between the sidewall and central separations. This is in agreement with the conclusion drawn from separate central and corner separation measurements by Funderburk & Narayanaswamy (2016). Due to the datasets only being available at the floor, it is not possible to directly assess the correlation of the two regions above the bottom wall on different wall-normal planes.…”
Section: Two-point Correlationssupporting
confidence: 86%
See 1 more Smart Citation
“…None of the surface pressure correlations, consistently between the experiments and simulations, show any indication of a low-frequency unsteady connection between the sidewall and central separations. This is in agreement with the conclusion drawn from separate central and corner separation measurements by Funderburk & Narayanaswamy (2016). Due to the datasets only being available at the floor, it is not possible to directly assess the correlation of the two regions above the bottom wall on different wall-normal planes.…”
Section: Two-point Correlationssupporting
confidence: 86%
“…Experiments have an advantage in this sense if longer run times are available; however it is difficult to obtain high resolution spatial data over a sizeable extent. Funderburk & Narayanaswamy (2016) experimentally investigated this link by taking pressure measurements under the central and corner separations of a compression ramp SBLI. Noting the differences in the cross-coherences of the power spectra under the most energetic locations at the centre and corner with locations upstream and downstream of them, they concluded that the separations behave independently of each other.…”
Section: Introductionmentioning
confidence: 99%
“…The SBLI for each model is generated through three different compression ramps with angles of 16°, 20°, and 24°. The ramps were made of low-carbon steel and attached to each model using two screws through the pair of oval slots shown in another member in the research group, in a 3D SBLI configuration with compelling results [23] which allowed for a strong start to the investigation undertaken by this study. Images from these experiments had to be taken after the run when the model could be removed.…”
Section: Compression Rampsmentioning
confidence: 99%
“…Figure 2.7 shows the set up for this form of measurement in the NCSU supersonic wind tunnel. This figureis adapted from Funderburk[22], and it should be noted that the model sidewall shown in the schematic are not present for this study. To provide a good contrast with the red pigment, all of the model surfaces were painted with a flat black background using a latex enamel spray paint from Krylon, Inc.…”
mentioning
confidence: 99%
See 1 more Smart Citation